23.0k views
4 votes
Factor completely.

4p²+36p+81
Question 3 options:

(2p−9)2

(2p+9)2

(4p+6)2

User Riyadh
by
5.4k points

2 Answers

6 votes
The Answer is:

(2+9)2
User Fath
by
5.2k points
7 votes

For this case we must factor the following expression:


4p ^ 2 + 36p + 81

We rewrite
4p ^ 2\ as\ (2x) ^ 2\ and\\ \\81\ as\ 9 ^ 2

So:


(2p) ^ 2 + 36p + 9 ^ 2

Verify the term of the medium:


2ab = 2 * (2p) * 9\\2ab = 36p

We factor using the perfect square trinomial rule:


a ^ 2 + 2ab + b ^ 2 = (a + b) ^ 2

Where:


a = 2p\\b = 9

So, we have:


(2p + 9) ^ 2

Answer:

Option b

User Bevor
by
5.7k points